2016 Joint Rail Conference 2016
DOI: 10.1115/jrc2016-5765
|View full text |Cite
|
Sign up to set email alerts
|

Field Measured Dynamic Effects and Load Distribution in a Prestressed Concrete Light Rail Bridge

Abstract: Live load performance of a recently constructed, prestressed concrete bridge was investigated to determine the Impact Factors (IMs), the Girder Distribution Factors (GDFs). The bridge was subjected to controlled static and dynamic loading using two Denver Transit Partners (DTP) electric-multiple-unit rail cars prior to a commuter rail line being placed into service. The rail cars travelled along northbound and southbound tracks of the four span, horizontally curved, bridge at various speeds. A total 24 tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Yuan et al 6 examined the behavior of prestressed concrete bridges (I-shape and box girders) subjected to light rail trains; however, the focus was on substructural responses. Khan et al 7 reported a preliminary field monitoring project with a bridge carrying light rail trains. The bridge consisted of four simply supported prestressed concrete girders at an average span of 95 ft (29 m).…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al 6 examined the behavior of prestressed concrete bridges (I-shape and box girders) subjected to light rail trains; however, the focus was on substructural responses. Khan et al 7 reported a preliminary field monitoring project with a bridge carrying light rail trains. The bridge consisted of four simply supported prestressed concrete girders at an average span of 95 ft (29 m).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the dynamic displacement were found to be as much as 20% larger than the corresponding static response, and the dynamic amplification factor (DAF) obtained from the moments reached a high value of 1.45. Khan et al [21] conducted field tests of a prestressed concrete simply supported beam bridge subjected to two electric-multiple-unit rail cars to determine the IMs, and the IMs were found to be insensitive to train speed and smaller than investigated code provisions. So far, much experimental research has been conducted to study the dynamic impact of railway arch bridges or simply supported bridges.…”
Section: Introductionmentioning
confidence: 99%